Psychometric Properties of the Korean Version of the Smoking Media Literacy Scale for Adolescents - Kim, Sookyung; Lee, Hyeonkyeong; Lee, Jung Jae; Hong, Hye Chong; Lim, Seungjoo; Kim, Junghee (Frontiers in Public Health, 2021)
Smoking media literacy has proven to be an effective competency for reducing adolescents’ smoking. This study aimed to cross-culturally modify the smoking media literacy scale and evaluate the validity and reliability of the Korean version of the revised Smoking Media Literacy Scale for Adolescents (K-SMLS). The translation of the K-SMLS was conducted according to the World Health Organization’s guidelines. After the translation process, an online survey was conducted with convenience samples of 215 total adolescents from five high schools in the capital city of Korea. Construct validity was examined by exploratory factor analysis and confirmatory factor analysis. Internal consistency reliability was examined with Cronbach’s alpha. The final version of the K-SMLS consisted of 15 items. The goodness of fit, determined through a confirmatory factor analysis of the three domains, was acceptable (χ2 = 237.85 (p < .001), CFI = .93, TLI = .92, RMSEA = .09, SRMR = .09). The reliability of the K-SMLS was satisfactory (Cronbach’s alpha =.78). The findings provide evidence for a valid and reliable tool that can be used to assess smoking media literacy in Korean adolescents. Further studies with a probability sampling design are suggested as the use of convenience samples limits the generalizability of the results to other populations.